Impact properties of low-alloy transformation-induced plasticity-steels with different matrix. Issue 10 (2nd July 2016) - Hojo, T.; Kobayashi, J.; Sugimoto, K.
Abstract : The effects of matrix types on Charpy impact properties were investigated in Fe–0.2%C–1.5%Si–1.5%Mn (mass%) transformation-induced plasticity steels. The steels with annealed martensite and bainitic ferrite matrix possessed higher upper shelf Charpy impact absorbed energy than the steel with polygonal ferrite and martensitic matrix. In addition, the low ductile–brittle fracture appearance transition temperatures were achieved in annealed martensite and martensite types in comparison with those of other steels.